Millennial Entrepreneurship Model in Islands: The Role of Digital Entrepreneur Ecosystem and Productive Entrepreneur in Realized Business Sustainability - Roky Apriansyah; Reniati reniati; Aimie Sulaiman; Hamsani Hamsani; Dian Junita; Dea Shafira Rakhman (International Journal of Applied Business and International Management, 2026)
This study examines how millennial entrepreneurship models are shaped by digital entrepreneurial ecosystems, productive entrepreneurship, and sustainable business orientation among MSMEs. It also explores the role of MSMEs in addressing unemployment in Indonesia and improving competitiveness in national and international markets. Using a quantitative approach, this research collected primary and secondary data from 174 millennial-owned food industry MSMEs across seven locations in the Bangka Belitung Islands. The sample was selected through purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that the digital entrepreneurial ecosystem has a positive and significant effect on productive entrepreneurship, while productive entrepreneurship strongly and significantly influences millennial entrepreneurship models. The digital entrepreneurial ecosystem and productive entrepreneurship also positively affect sustainable business. In addition, sustainable business has a significant relationship with millennial entrepreneurship, confirming the importance of sustainability in strengthening business performance, resilience, and competitiveness. The research model demonstrates moderate explanatory and predictive power for sustainable business and millennial entrepreneurship. This study concludes that strengthening digital entrepreneurial ecosystems and increasing entrepreneurial productivity are key factors in developing sustainable millennial entrepreneurship in island regions. The integration of digital ecosystems, entrepreneurial productivity, and sustainability orientation can enhance the resilience and long-term viability of MSMEs. Theoretically, this research enriches entrepreneurship literature by developing a millennial entrepreneurship model based on digital ecosystems and sustainability in an archipelagic context. Methodologically, it strengthens the application of PLS-SEM in MSME studies, while practically, it provides policy insights for local governments and stakeholders in designing digital-based and sustainability-oriented MSME development strategies. Its limitation lies in its focus on MSMEs in a single archipelagic province and its cross-sectional design, which limits the ability to capture long-term entrep